(untitled) (The International Journal of Educational Sciences and Arts, 2026)
This study aims to examine the relationship between patterns of Saudi audience interaction with AI-generated content and their implications for the nature of digital relationships within Saudi society. The study is grounded in a central research problem: the accelerating reliance of individuals and institutions on algorithmic content, including personalized advertisements, intelligent visual designs, and interactive chatbots, and the resulting transformations in social communication patterns, digital family cohesion, digital value systems, and levels of cyber social trust and safety. The study adopts a descriptive-analytical method within a quantitative research framework, using an electronic questionnaire as the main tool for data collection. The target population consists of Saudi users of digital platforms and artificial intelligence applications. A random sample of no fewer than 384 respondents is proposed, based on the Krejcie and Morgan formula. The study employs a five-point Likert scale to measure respondents’ attitudes toward the dimensions of AI-generated content, including algorithmic personalization, creative and visual attraction, and automated interactivity, as well as their perceived social implications for digital relationships. The significance of this study lies in its attempt to conceptualize “smart digital relationships” as an emerging form of social connection shaped through non-human algorithmic mediation. It also contributes to a deeper understanding of the social, cultural, and security-related implications of audience interaction with intelligent content in Saudi society. Furthermore, the study offers practical insights that may assist media institutions, social organizations, and decision-makers in managing public interaction with artificial intelligence technologies in ways that enhance the quality of human relationships, preserve social values, and support the development of a safe and balanced digital environment in alignment with the objectives of Saudi Vision 2030.